2004
DOI: 10.1111/j.1525-1594.2004.47260.x
|View full text |Cite
|
Sign up to set email alerts
|

Arresting Dialysis‐Related Amyloidosis: A Prospective Multicenter Controlled Trial of Direct Hemoperfusion with a β2‐Microglobulin Adsorption Column

Abstract: We investigated the clinical efficacy of direct hemoperfusion with a beta2-microglobulin (beta2-m) adsorption column for the treatment of patients with dialysis-related amyloidosis. A 2-year prospective controlled study was performed to compare the effects of passaging blood through a (beta2-m) adsorption column (Lixelle) before it is passaged through the dialysis polysulfone membrane on the severity of amyloidosis in these individuals. Patients (n = 22) whose blood went through the Lixelle column prior to dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
0
31
1
1
Order By: Relevance
“…In some studies, dialysis by HDF and hemofiltration, which may contribute to the decrease of serum β 2 MG levels - or dialysis by β 2 MG absorption column - were reported to possibly decrease the incidence of DRA or its progression [6,37,38]. However, the patients in our study who received HDF had higher ORs for CTS surgery than did those receiving standard HD.…”
Section: Discussioncontrasting
confidence: 54%
“…In some studies, dialysis by HDF and hemofiltration, which may contribute to the decrease of serum β 2 MG levels - or dialysis by β 2 MG absorption column - were reported to possibly decrease the incidence of DRA or its progression [6,37,38]. However, the patients in our study who received HDF had higher ORs for CTS surgery than did those receiving standard HD.…”
Section: Discussioncontrasting
confidence: 54%
“…DRA is recognized as a serious complication in patients on long-term HD and results in the development of carpal tunnel syndrome, bone cysts, destructive spondyloarthropathy, and joint pain, with functional disturbances such as limitation of motion [10]. However, there is no information on whether b 2 M induces the systemic inflammatory response in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that treatment with a high-flux dialyzer and a low-contaminant dialysis fluid yielded a lower β 2 m level and inhibited the onset of bone cysts compared with conventional HD [14,15,16]. Gejyo et al [4] reported an increase in number of bone cysts in a group given HD alone, but no additional formation of bone cysts in a group treated with Lixelle for 2 years. The difference in efficacy of treatment of bone cysts in the wrist and hip joints appears to be due to the differences in weight load among joints.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects on bone cysts, improvements in ADL and pain score and decrease in frequency of nocturnal awakening were achieved as well. Although the SF-36 is the most widely used generic health status measure, and finding on physical function, pain and fatigue to evaluate the severity of rheumatoid arthritis (RA) and DRA symptoms, several studies have used m-HAQ [4,5], which is well validated with other instruments (visual analogue pain scale (Vas), SF-36, and grip strength). Thus, in this study, we selected m-HAQ as a generic measure of the health status of patients with DRA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation